PENDAMPINGAN MANAJEMEN SDM PADA TK TUNAS RIMBA PERHUTANI UNTUK MENINGKATKAN KEMAMPUAN LITERASI DAN NUMERASI SISWA SEJAK USIA DINI - Gayatria Oktalina; Agnisa Widayanti; Fitra Jaya; Yati Yati; Sucipto Sucipto (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
This community service program aimed to improve human resource management at TK Tunas Rimba Perhutani in Indramayu as an effort to enhance early childhood literacy and numeracy. The program was implemented involving the kindergarten’s Tunas Rimba Perhutani Cabang Indramayu principal and teachers. The assistance approach included training sessions, workshops, direct mentoring, and participatory evaluation. The results indicated an improvement in teachers’ understanding of HR management and literacy-numeracy teaching techniques. Teachers became capable of designing more structured and creative literacy and numeracy programs, and produced simple learning media to support these activities. Student participation in daily reading and counting activities also increased after the implementation of more varied and enjoyable learning methods. Overall, this program helped the partner kindergarten strengthen its educational management, which is expected to positively impact the literacy and numeracy skills of the students from an early age.